2007
DOI: 10.1007/s10689-007-9126-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of patient users in cancer genetics services in primary care

Abstract: There is much research that suggests all aspects of health care in the National Health Service should have patient user experience and input. This is to make sure service provision meets the needs of the local population. The Oldham Cancer Genetics team felt this was very important when developing a new service. Involving "patient users" meant the service kept the "client" at the centre of the planning process. It ensured all locally produced leaflets, family history questionnaires and patient pathways were ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Ten studies described case-based evidence that participation in an advisory council had a therapeutic or positive benefit for the patients themselves [ 8 , 9 , 36 , 38 44 ]. A report of interviews with members of a children’s hospital teen advisory council found that participation fostered organizational skills and professional development [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ten studies described case-based evidence that participation in an advisory council had a therapeutic or positive benefit for the patients themselves [ 8 , 9 , 36 , 38 44 ]. A report of interviews with members of a children’s hospital teen advisory council found that participation fostered organizational skills and professional development [ 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Seventeen studies described how patient advisors helped develop materials for patient education or self-management [ 8 , 9 , 24 – 28 , 30 , 31 , 40 , 42 , 45 – 50 ]. Fifteen studies described how patient advisors recommended changes to a healthcare setting’s physical space, such as an improved waiting room, improved accommodations for physical disabilities, or improved layout [ 13 , 27 30 , 32 , 33 , 35 , 40 , 41 , 48 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation